Editorial - Mostert, Nicky (Journal of Health Informatics in Africa, 2026)
Editorial to JHIA Vol. 12 (2025) Issue 2 Nicky Mostert Nelson Mandela University, Gqeberha, South Africa The Journal of Health Informatics in Africa (JHIA) continues to provide a scholarly platform for research that advances the design, implementation, governance, and evaluation of health information systems within African and comparable low- and middle-income country contexts. Volume 12, Issue 2 reflects the journal’s sustained focus on digital health adoption, health information system governance, data quality, and evidence-based decision-making, with contributions spanning empirical studies, methodological validation, governance frameworks, and systematic reviews. Collectively, the papers in this issue highlight both the transformative potential of digital health technologies and the structural, social, and data-quality challenges that continue to shape their impact. Several contributions underscore the importance of moving beyond technical implementation toward user engagement, trust, governance, and data integrity as foundational elements of sustainable digital health systems. Research by Kanny and Adebesin explores user engagement with mobile health applications for diabetes self-management within a South African context. Using a quantitative design, the study applies principal component analysis to validate the User Engagement Scale (UES) in a local mHealth setting. The findings confirm the multidimensional nature of user engagement, encompassing factors such as focused attention, perceived usability, and aesthetic appeal. The paper contributes methodologically by demonstrating the contextual applicability of an established engagement scale and substantively by reinforcing the role of user-centred design in promoting sustained mHealth use for chronic disease management. Focusing on governance at the community level, Chumba et al. examine structural mechanisms within a community-based health information system (CBHIS) using a mixed-methods approach. The study explores how governance practices influence data use, accountability, and service delivery, highlighting the importance of clearly defined roles, stakeholder participation, and coordination structures. By foregrounding community-based systems, the paper extends health informatics governance scholarship to an area that is critical for primary healthcare delivery but often underrepresented in the literature. A broader perspective on digital service delivery is provided by Alton Mabina, who present a systematic literature review on trust and access in telemedicine. Synthesising findings from 32 peer-reviewed studies published between 2018 and 2025, the review shows that telemedicine initiatives frequently improve access to care, particularly in rural and underserved settings. However, sustained adoption is constrained by trust-related concerns, including privacy, data security, cultural alignment, and provider–patient relationships. The paper highlights the interdependence of access and trust and emphasises the importance of participatory, user-centred approaches in telemedicine design and implementation. Extending the discussion to a continental scale, Oladosu et al. offer a systematic review of digital health innovations across Africa, drawing on evidence from 68 studies published between 2014 and 2025. The review maps the prevalence of mHealth, telemedicine, electronic health records, and emerging artificial intelligence applications, with a strong concentration in maternal and child health, infectious disease management, and chronic care. While improvements in efficiency and service delivery are reported, persistent challenges related to infrastructure, digital literacy, financing, and regulation are identified. This paper provides a macro-level context that complements the more focused empirical studies in the issue. Issues of data integrity and health system decision-making are addressed by Tungbani and Nhlapo, who assess the quality of cause-of-death data in Ghana’s District Health Information Management System II (DHIMS II) using 2023 institutional mortality records coded with ICD-11. Applying the WHO’s ANACOD3 tool, the study reveals that non-communicable diseases account for the majority of recorded deaths, reflecting Ghana’s epidemiological transition. At the same time, substantial data quality limitations are identified, with over 30% of records classified as ill-defined or unusable “garbage codes.” The paper demonstrates how systematic quality assessment tools can identify structural weaknesses in mortality reporting and support more reliable, evidence-based health planning. In addition to the scholarly contributions presented in this issue, JHIA is pleased to announce an important change to its publication model. From January 2026, the journal will adopt a continuous publication approach, whereby articles will be published as soon as they are accepted and finalised, rather than being held for biannual issues. Historically, JHIA published two issues per year, released at six-month intervals. The move to continuous publication is intended to reduce time to publication, improve the timeliness of research dissemination, and better serve authors, readers, and the broader health informatics community. Accepted articles will continue to be organised within annual volumes, but publication will no longer be constrained by fixed issue schedules. This change aligns JHIA with evolving scholarly publishing practices and supports more responsive engagement with rapidly developing digital health and health information system research. Volume 12, Issue 2 reflects the growing maturity and diversity of health informatics research in Africa. The papers collectively emphasise that technological innovation must be accompanied by strong governance, user engagement, trust, and high-quality data to realise meaningful and sustainable health system improvements. We thank the authors, reviewers, and editorial team for their continued contributions to the journal and look forward to advancing timely, impactful scholarship through JHIA’s new continuous publication model. Nicky Mostert December 2025